Targeting PGK1 as a Novel strategy to regulate the sensitivity of HER2 positive gastric cancer to lapatinib - Ni, Xiaochen; Zhang, Kaiyuan; Huang, Xueru; Zhang, Mingsi; Guo, Jianing; Fan, Wei; Wang, Chuhang; Du, Zhongyan; Jiang, Tao; Zhang, Guangji (Frontiers in Pharmacology, 2025)
HER2 is amplified in approximately 20% of gastric cancers, and these patients exhibit a favorable response to trastuzumab treatment. Lapatinib, as a HER2-targeted drug, demonstrates potent inhibitory effects on HER2-addicted N87 gastric cancer cells. However, lapatinib has not shown significant advantages in clinical trials. Our study revealed that the expression of the key glycolysis gene PGK1 negatively correlates with the sensitivity of tumor cells to lapatinib. Both genetic regulation of PGK1 and pharmacological inhibition of lactate secretion can enhance the inhibitory effect of lapatinib on N87 cells, whereas overexpression of PGK1 attenuates the efficacy of lapatinib. Modulating PGK1 expression in N87 cells exposed to lapatinib affects the activation level of AKT, a downstream effector of HER2, and consequently influences the viability of N87 cells. This study indicates that regulating the expression levels of PGK1 impacts the sensitivity of HER2-positive gastric cancer to lapatinib, and potentially serving as a therapeutic strategy for HER2-positive gastric cancer patients who do not respond to lapatinib.